SHOPAHOLIC IN THE MIDST OF EDUCATIONAL AID: A STUDY ON CONSUMERISM OF STUDENTS WHO RECEIVE KIP-LECTURE AT UNIVERSITAS MALIKUSSALEH - Sitompul, Chairotun Nisa; Nirzalin; Cut Rizka Al Usrah; Bobby Rahman; Fakhrurrazi (FISIP Universitas Malikussaleh, 2025)
This study examines the Shift in the Meaning of Commodity and Shopaholic Among KIP-Lecture Recipients (Student Study of the Faculty of Economics and Business, Malikussaleh University). The purpose of this study is to find out the shopping practices and motivations that drive students' consumptive actions. The approach in this study is a qualitative method using a case study phenomenological approach using Jean Baudrillard's theory of Consumption Society about consuming sign values instead of functional values. In a postmodern society, consumption is no longer a pure object. As in the results of this study, students consume clothes as fashion and consume other commodities in the form of skincare, and cosmetics. The consumption carried out by students is not to meet needs but the desire and value of the signs contained in the commodities consumed. Some of the motivations of students in acting consumptive include the need for social recognition (validation), wanting to look beautiful, desire, Fear of Missing Out (FoMO), and Prestige.